(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This paper explores the potential of Sketchfab as a tool for visualizing technical processes in the educational environment, focusing on its application in STEM and technology education. The research examines how the platform's 3D modeling and visualization capabilities can enhance learning outcomes by fostering better understanding of complex technical concepts and improving spatial reasoning. The study is grounded in the context of the increasing digitalization of education and the integration of immersive technologies in teaching practices. The research employs a mixed-methods approach, combining quantitative analysis of user engagement statistics with qualitative interviews and surveys conducted with both teachers and students. Statistical data were collected on the number of users, their purposes for using Sketchfab, and the time spent engaging with the platform. Additionally, perceptions of Sketchfab’s impact on learning outcomes were assessed, focusing on its role in enhancing student motivation, improving understanding of technical content, and developing spatial thinking. Results indicate a significant increase in the adoption of Sketchfab among educators and learners between 2023 and 2024, with teacher usage rising by 40% and student engagement growing by 37.5%. The platform is primarily utilized for visualizing 3D models, facilitating project-based learning, and enhancing laboratory work. Students reported a high level of satisfaction, with 85% agreeing that Sketchfab improved their understanding of complex subjects and 90% indicating that it contributed to the development of their spatial thinking. The findings suggest that Sketchfab offers valuable pedagogical benefits, particularly in technical and STEM education. By providing an interactive, immersive learning experience, it enables students to visualize abstract concepts and engage in hands-on learning, thus supporting constructivist approaches to education. The platform’s integration into instructional design not only enriches content delivery but also fosters a student-centered learning environment. In conclusion, Sketchfab represents a promising tool for the visualization of technical processes in education. However, its full potential requires further exploration through long-term studies and the development of methodological guidelines for its effective use in various educational settings. Recommendations for educators include incorporating 3D modeling as a central element in project-based learning and utilizing Sketchfab to facilitate collaborative problem-solving tasks.